Follow-up of erlotinib related uveitis. (14th August 2012) - Kumar, Indu; Ali, Kashif; Usman-Saeed, Muniba; Saeed, Muhammad Usman
Abstract : The authors report the follow-up of a 68-year-old lady with bilateral anterior uveitis secondary to erlotinib. Erlotinib was started and stopped after symptoms and signs suggestive of severe bilateral anterior uveitis were noted. The patient developed signs of a non-ST elevation myocardial infarction, 12 days after stopping the erlotinib, and recovered without major problems. The patient also reported intermittent low-grade fever since starting erlotinib which resolved after stopping this drug. No further symptoms of uveitis were noted up to 6 month follow-up. The patient reported improved well being, resolution of ocular symptoms and intermittent low-grade fever at last follow-up (6 months after stopping erlotinib).